Configuration of the level of metacognitive appropriation of pedagogical knowledge in the initial teaching training (Praxis Educativa, 2020)
The study characterizes the level of metacognitive appropriation of pedagogical knowledge of the Pedagogy students. For this, it was used an instrument deliberately designed for the research, with a Likert type rating scale that inquiries into the metacognitive appropriation of pedagogical knowledge. The instrument considered conceptual, procedural, and attitudinal components, based on performance indicators. The test was applied through a computational skill to 107 students of Pedagogy programs. It accomplished the validation, application, and analysis of results, extracting the Cronbach’s alpha coefficient value of 0.933 from 31 items; apart from the interpretative analysis of the students’ answers. The diagnosis reported on the level of pedagogical knowledge, with a tendency of medium performance in the three programs. The results have allowed to identify students’ strengths and weaknesses, reorienting the subjects based on cognitive emptiness, professional skills and attitudes.
Keywords: cognitive process; evaluation; pedagogical research; teacher competences